R PENGEMBANGAN POTENSI USAHA KRIPIK TALAS TIGA PUTRA DI DESA LEMBUAK - Endang Kartini; Baehaki Syakbani; I Made Suardana; Ni Nyoman Yuliati; Rusli Amrul; Yuli Astini; Imam Samudra; Dina Wijayanti (Valid Jurnal Pengabdian, 2026)
Business mentoring for the Tiga Putra chips business in Lembuak Village, Narmada District, West Lombok is a community service program conducted by lecturers at STIE AMM Mataram. This mentoring program aims to improve the group's understanding of the problems that arise in running a taro chip business. Problems that emerged during the mentoring program included the lack of a clear plan for developing the taro chip business, resulting in unclear goals and targets. This community service program employed digital marketing promotion and limited access to collaborations with other parties. The method used for this service was counseling and mentoring for the business group. The results of this service program include an understanding of business management, digital marketing, and collaboration with other parties to develop the taro chip business.